Exploring typologies for consultation performance for learning and assessment in medical training: Presenter(s): Angelique Timmerman, Maastricht University, Netherlands. (April 2023) - van der Vleuten, Cees; Pawlikowska, Teresa; Muris, Jean
Abstract : Background: Objective is to explore typologies for consultation performance describing holistic behavioural patterns of consultation performance of trainees over time and identify challenges for future learning. Methods: A qualitative study was conducted in Family Medicine residency training consisting of three phases: 1. From year 1 (N=6) and year 3 (N=7) trainees four videotaped consultations were selected from 80 in total, and classified for consultation performance on dimensions medical expertise and doctor patient interaction, 2. During an individual interview clinical supervisors (N=20) observed these consultations and reflected on present trainee behaviours, 3. Four narrative profiles were developed and analysed against pre-existing typologies on similar and different present consultation behaviours. (1) Findings: Four narrative profiles describing trainee attitude and consultation behaviours were validated and recommendations for future learning formulated. Central features of the profiles were doctor-patient interaction explicated in relationship building, exploring, structuring, and shared decision making, with medical expertise as a moderating factor. Discussion: There is a shared frame of reference between clinical supervisors on behavioural patterns mirroring proficiency in doctor patient interaction. Learning challenges focus on balancing patient-centeredness with effectively working on clinical tasks, while outlining the developmental route for contextual adaptation. The narrative profiles may support providing rich and tailored feedback on consultation performance and stimulate longitudinal monitoring of individual learning during medical training. 1.Oerlemans M, Dielissen P, Timmerman A, Ram P, Maiburg B, Muris J, Vleuten, C., van der. Should we assess clinical performance in single patient encounters or consistent behaviors of clinical performance over a series of encounters? A qualitative exploration of narrative trainee profiles. Medical Teacher. 2017;39(3):300-7.